How Phase theory can be used to improve reading comprehension in children - Monal Manik Dewle (International Journal of Language Teaching and Education, 2018)
The present paper gives summary about some development theories which focuses on how development of reading takes place in a child. It then focuses on one particular theory, i.e. the Phase theory by Ehri (1999) where this theory mentions with the help of four stages how a child goes from the stage of no knowledge of letters to full knowledge of letters in children. Though this theory has been criticized by some but it is still considered as the theory which explains the basic stages of development in a child while reading while refuting the earlier theories on development of reading. Further, this paper discusses how this theory can be used as a form of instruction for children to develop reading comprehension.